ANALYSIS OF THE GHAZALS IN “DAHNOMA” BY YUSUF AMIRIY (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Yusuf Amiriy, the great representative of the 15th century, is considered a prolific creator, a master of words both in verse and prose. His work includes poetic works of various genres. In particular, the poet's ghazals have a special place in classical Turkish poetry due to their artistry, subject direction and originality of images. In the article, some of the ghazals from the work “Dahnoma” are analyzed.